Land‐Applied Swine Lagoon Sludge Impacts Soil Concentrations and Crop Uptake of Zinc and Copper. Issue 1 (1st December 2013) - Israel, Daniel W.; Smyth, T. Jot; Hardy, David H.
Abstract : Swine lagoon sludge applications to crop land are based on N requirements of the receiver crop. Since sludge Cu and Zn concentrations exceed levels required for optimum crop production, repeated application to the same field could result in toxic levels of soil Zn and Cu. Our objectives were to evaluate the impact of swine lagoon sludge application to corn ( Zea mays L.) on Zn and Cu concentrations in the soil, accumulation in the crop and removal from the field in grain. Sludge rates generated treatments that ranged from 165 to 655 kg total N ha −1, from 22 to 88 kg Zn ha −1, and from 14 to 54 kg Cu ha −1 . The optimum N rate for grain yield at the test site was 327 kg N ha −1 . The slope for the increase in Mehlich‐3 extractable soil Zn to applied Zn was 3‐fold greater than the slope for the increase in Mehlich‐3 extractable soil Cu to applied Cu. Stover contained higher Zn and Cu concentrations and accumulated larger amounts of total Zn and Cu than grain. Zinc and Cu removal in grain of one crop compared to amounts applied at the agronomic N optimum (327 kg N ha −1 ) indicates that cropping for decades to centuries would be required to lower soil Zn and Cu levels to pre‐application levels. Therefore, application of swine lagoon sludge to crop land must be managed to avoid increases in Mehlich‐3 extractable soil Zn and Cu to phytotoxic levels.